Investigation of the influence of Fe2B layer thickness on the enhancement of tribological behavior of borided EN-GJL-250 cast iron: a comprehensive investigation under optimized lubrication - Charmati, Djihad; Tlili, Samira; Touhami, M. Z.; Bourebia, Mounira; Kaleli, Emrullah Hakan (SPRINGER LONDON LTD, 2023)
In general, the improvement of mechanical and tribological properties of functional surfaces is achieved by mechanical, thermal, or thermochemical treatments. In the present work, the advancement of the aforementioned properties is carried out using the boriding process. This experimental work aims to study the effect of single-phase Fe2B layer thickness on the EN-GJL-250 cast iron tribological behavior through optimized lubrication under normal load of 60 N at 100 degrees C. The specimens were borided at 950 degrees C for 1 and 4 h by a pack-boriding method using a mixture of B4C 85 wt% and Na2CO3 15 wt%. Advanced experimental techniques and comprehensive surface and tribological evaluations were used in this study: The surfaces of the samples were characterized by XRD, SEM, and microhardness measurements. A scratch test and a Daimler-Benz Rockwell C Adhesion Test were used for adhesion testing, and tribological tests were performed using an alternative tribometer. The XRD analysis revealed the formation of a monophase Fe2B layer, as evidenced by the results obtained. The optimum tribological behavior was obtained at a temperature of 950 degrees C/4 h, showing a remarkable reduction in wear rate of about 300 times compared to both the treatment at 950 degrees C/1 h and the unborided state.
Keywords: Fe2B; Wear resistance; Tribology; Lubricant; Adhesion; ABRASIVE WEAR BEHAVIOR; FRICTION; RESISTANCE; SCRATCH; STEEL; CHROMIUM; KINETICS; ALLOY; Automation & Control Systems; Engineering